Socioeconomic inequalities in health outcomes among Thai older population in the era of Universal Health Coverage: trends and decomposition analysis - Kaikeaw S. (2023)
BACKGROUND: Thailand's Universal Health Coverage (UHC) has been achieved since 2002 when the entire population are covered by three main public health security schemes: (1) Civil Servant Medical Benefit Scheme (CSMBS); (2) Social Security Scheme (SSS); and (3) Universal Coverage Scheme (UCS). Citizens have access to healthcare services at all life stages and are protected from catastrophic expenditure and medical impoverishment. However, there are health inequalities in both health outcomes and access to healthcare among older Thais. This study aims to: (1) assess the degrees of socioeconomic inequalities in health outcomes among the older Thai population during the period of Thailand's UHC implementation (2003-2019), and (2) explain socioeconomic inequalities in health outcomes through decomposition of the contributions made by Thailand's UHC policy and other health determinants. METHODS: Data sets come from a four-year series of the National Health and Welfare Survey (HWS) between 2003 and 2019. The health outcome of interest was obtained from the Thai EQ-5D index. The Erreygers' concentration index (CI) was used to calculate the socioeconomic inequality in health outcomes. Multivariate methods were employed to decompose inequalities. RESULTS: Findings indicated Thai older adults (aged 50 and older) are healthier during the UHC implementation. Better health outcomes remain concentrated among the wealthier groups (pro-rich inequality). However, the degree of socioeconomic inequalities in health outcomes significantly declined by almost a factor-of-three (from CI = 0.061 in 2003 to CI = 0.024 in 2019) after the roll-out of the UHC. Decomposed results reported that Thailand's UHC, urban residence, and household wealth were major contributors in explaining pro-rich inequalities in health outcomes among Thai older adults. CONCLUSIONS: Older persons in Thailand have better health while health inequalities between the rich and the poor have substantially decreased. However, there is inequalities in health outcomes within all three national health security schemes in Thailand. Minimizing differences between schemes continues to be a crucial cornerstone to tackling health inequalities among the older population. At the same time, making Thailand's UHC sustainable is necessary through preparing financial sustainability and developing health resources to better serve an ageing society.